PERBAIKAN NILAI KUAT TEKAN BIOKERAMIK SCAFFOLD HIDROKSIAPATIT MENGGUNAKAN TREATMENT PLASMA DBD - Dica A. Nurmanta; Masruroh Masruroh; D.J. Djoko H. Santjojo (Universitas Islam Balitar Blitar, 2021)
On type of Plasma is a Plasma DBD which is generated at atmospheric pressure. Scaffold hydroxyapatite (HA) is a bioceramic which widely developed nowadays in applications. The pores that are owned in the scaffold can effect a mechanical properties, namely compressive strength. Treatment by using Plasma DBD method is expected to have a good improvement to interconnected porous so as to improve the compressive strength of the bioceramic scaffold HA. In this study, we use 3 different time variations are 20 minutes, 25 minutes dan 30 minutes in Plasma DBD treatment to determine the effect of each variations. Pore analysis and compressive strength test will be carried out before and after Plasma DBD treatment. The surface morphology of the scaffold HA was observed by using a Field Emission – Scanning Electron Microscope (FE-SEM), composition by using EDX and compressive strength was observed by using compressive strength test. The result showed that the compressive strength of bioceramic scaffold HA increase relatively to increase of the treatment time.